Complications of Peripheral Cannulation Site in Obese Patients on Adult Extracorporeal Membrane Oxygenation. Issue 12 (December 2021) - Alvarez, Nkosi H.; O'Malley, Thomas J.; Abai, Babak; Salvatore, Dawn M.; DiMuzio, Paul J.; Hirose, Hitoshi
Abstract : Placement of extracorporeal membrane oxygenation (ECMO) in obese patients has been challenging; however, cannulation risk in obese patients has not been clearly investigated. We therefore explored ECMO cannulation complications in this obese population. Data were reviewed from adult ECMO database from 2010 to 2019. Patients were stratified by body mass index (BMI) (normal weight [NW] [BMI 18.5–24.9], overweight [BMI 25–29.9], class I [BMI 30–34.9], class II [BMI 35–39.9], class III [BMI >40]). Patients with central cannulation were excluded from this study. Combined ECMO cannulation complications and survival data were retrospectively analyzed. There were 233 patients, 156 venoarterial (VA) ECMO patients (45 [28%] NW, 51 [33%] overweight, 37 [24%] class I, 12 [8%] class II, and 11 [7.0%] class III) and 77 venovenous (VV) ECMO patients (14 [18%] NW, 13 [17%] overweight, 17 [22%] class I, 11 [14%] class II, and 22 [29%] class III). There were significantly more cannulation site bleeds in VA class III (55%) patients compared with VA NW patients (22%), p = 0.006. There was no significant difference in cannulation site bleeding between BMI groups for VV ECMO. There was no difference in 30 day mortality, ECMO survival for all BMI groups in both VA and VV ECMO. There is significant increased risk of bleeding with peripheral VA cannulation of obese patients with BMI > 35. Cannulating surgeon should be aware of this bleeding risk in morbidly obese patient who undergo VA ECMO.